Effect of Transcutaneous Electric Nerve Stimulation over the Stellate Ganglion: A Placebo-Controlled Double Blind Study in Healthy Subjects - Schuhfried, O.; Herceg, M.; Vacariu, G. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2012)
Does transcutaneous electric nerve stimulation (TENS) over the stellate ganglion influence the function of the autonomic nervous system?12 healthy subjects (6 female, 6 male) received according to a randomization list (cross-over design) either conventional TENS therapy (100 Hz biphasic) or a placebo application (device switched on, but current intensity zero) over the stellate ganglion of the non-dominant side for 20 min on 2 different days. Before and after the interventions the pain threshold was determined by pressure algometry on the forearm. Skin temperature was recorded by infrared thermography in the dorsum of the hand and the distal phalanx of the middle finger of the treated arm before and immediately after 20 min of intervention. After this, alterations of skin temperature were measured 1 min as well as 5 min after a Valsalva like manoeuvre. At the same time points the heart rate was measured using a pulse recorder.After the intervention temperature assessment in the dorsum of the hand showed higher values (given as differences compared to baseline values before the intervention) with TENS treatment than with placebo treatment at all time points of measurement. For temperature values in the dorsum of the hand repeated-measures analysis of variance showed a significant effect both between the interventions (p=0.046) and over time (p<0.0001). For the temperature assessment in the distal phalanx of the middle finger no significant effect between the 2 interventions was found. Furthermore there were no statistically significant differences with regard to the measurement of the pain threshold and the heart rate data (given as differences compared to baseline values before the intervention).Conventional TENS application over the stellate ganglion leads to a significantly higher skin temperature in the dorsum of the hand as compared to placebo application in healthy humans. This suggests that this therapeutic application may inhibit sympathetic outflow from the stellate ganglion.
Keywords: skin temperature; stellate ganglion; sympathetic nervous system; thermography; transcutaneous electrical nerve stimulation